4(6y+2)-6=-2

Simple and best practice solution for 4(6y+2)-6=-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(6y+2)-6=-2 equation:


Simplifying
4(6y + 2) + -6 = -2

Reorder the terms:
4(2 + 6y) + -6 = -2
(2 * 4 + 6y * 4) + -6 = -2
(8 + 24y) + -6 = -2

Reorder the terms:
8 + -6 + 24y = -2

Combine like terms: 8 + -6 = 2
2 + 24y = -2

Solving
2 + 24y = -2

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 24y = -2 + -2

Combine like terms: 2 + -2 = 0
0 + 24y = -2 + -2
24y = -2 + -2

Combine like terms: -2 + -2 = -4
24y = -4

Divide each side by '24'.
y = -0.1666666667

Simplifying
y = -0.1666666667

See similar equations:

| -8x-1.2=-7x-14.7 | | 16-48+4= | | 2(9+24)=30 | | -7+5(1+6x)=-39-7x | | .20(x-200)=160 | | 5x+3=48findx | | .20(x-200)=575 | | (9x^3-27x)(-4x-12)=0 | | 4a-5whena=9 | | 36x^2+24x=7 | | 3a-2(0)=18 | | 2s^2-7s+6=0 | | X(x+3)-(2x*x)=28 | | 5(0)+b=10 | | 5a+y=10 | | 3(2d-7)=2(2+4d) | | 3x^2+2x-42.001=0 | | 2x+(x-9)-2(X+3)=0 | | Q+q+q=q+4 | | 8m-11=21 | | -9x-2.3=-8x-1.6 | | 5+678= | | y+1.1=8.69 | | 4x^2+2x-41.999=0 | | 63-v=203 | | x-7.7=1.8 | | x*110+0.5x*30+0.25x*80=26100 | | 8.1-2k=10.5 | | -2x+6=10x+14 | | -8x+2=-3x+-14 | | (x+1)x^2=0 | | -2(t-7)-(t+4)=3 |

Equations solver categories